Studi Karakteristik Arus Lalulintas Simpang Tak Bersinyal Jalan Menur Pumpungan Surabaya - Wibisono, R. Endro; Huda, Miftachul (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
Phase determination and traffic control systems are usually more emphasized at locations where road intersections or intersections occur. Because at the meeting of two or more roads this results in a point of conflict that ultimately results in traffic jams. The purpose of this study is to overcome the traffic congestion on Jalan Menur Pumpungan required a good traffic regulation in terms of the level of service and safety for motorists. The method used unsigned intersection performance in this study refers to the source of the Indonesian Road Capacity Manual (MKJI 1997). The results of this study indicate the degree of saturation of the Menur Pumpungan Intersection in 2019 DS is 0.58. For forecasting the coming year in 2021 DS will be 0.75. While in 2031 DS 0.95. Level of service (Los) for each intersection in 2019 is DS = 0.58 and Los = C (Enough), in 2021 it is DS = 0.75 Los = C (Enough), while in 2031 it is DS = 1.211 and Los = D (Less).